2019
DOI: 10.1002/dta.2614
|View full text |Cite
|
Sign up to set email alerts
|

Elimination profile of triamcinolone hexacetonide and its metabolites in human urine and plasma after a single intra‐articular administration

Abstract: Triamcinolone hexacetonide (THA) is a synthetic glucocorticoid (GC) used by intra‐articular (IA) administration. GCs are prohibited in sports competitions by systemic routes, and they are allowed by other routes considered of local action (IA administration, among others). The aim of the present work was to study the metabolic profile of THA in urine and plasma following IA administration. Eight patients (4 males and 4 females) with knee osteoarthritis received an IA dose of THA (40 mg) in the knee joint. Spot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
25
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 35 publications
(124 reference statements)
3
25
0
Order By: Relevance
“…A considerable number of studies into urinary glucocorticoid eliminations following the administration of different drug formulations and varying routes of administration has been conducted, supporting today's result interpretation in case of AAFs related to glucocorticoids as necessitated by the permitted use of glucocorticoids during out‐of‐competition periods as well as via routes that are not considered to result in systemic effects and effective blood concentrations 31–36 . To date, AAFs concerning glucocorticoids are issued when a glucocorticoid is detected at concentrations exceeding the reporting level of 30 ng/mL, 3 thus largely disregarding the potencies and correspondingly required therapeutic dosages of glucocorticoids.…”
Section: Proof‐of‐principle Pilot Study Data – Prednisone/prednisolonementioning
confidence: 96%
“…A considerable number of studies into urinary glucocorticoid eliminations following the administration of different drug formulations and varying routes of administration has been conducted, supporting today's result interpretation in case of AAFs related to glucocorticoids as necessitated by the permitted use of glucocorticoids during out‐of‐competition periods as well as via routes that are not considered to result in systemic effects and effective blood concentrations 31–36 . To date, AAFs concerning glucocorticoids are issued when a glucocorticoid is detected at concentrations exceeding the reporting level of 30 ng/mL, 3 thus largely disregarding the potencies and correspondingly required therapeutic dosages of glucocorticoids.…”
Section: Proof‐of‐principle Pilot Study Data – Prednisone/prednisolonementioning
confidence: 96%
“…Similarly, the metabolic transformation and elimination of triamcinolone acetonide (TA) as well as triamcinolone hexacetonide (THA) was studied, with TA being administered either intranasally (220 μg/day for 3 days) or intramuscularly (single dose, 40 mg), 165 and THA intraarticularly (single dose, 40 mg) 166 . Urinary TA concentrations remained below 3.5 ng/ml upon intranasal administrations, while the main metabolite 6β‐hydroxytriamcinolone increased to 93 ng/ml.…”
Section: Corticoids and Cannabinoidsmentioning
confidence: 99%
“…Urinary TA concentrations remained below 3.5 ng/ml upon intranasal administrations, while the main metabolite 6β‐hydroxytriamcinolone increased to 93 ng/ml. Conversely, the intramuscular drug administration resulted in urinary TA concentrations up to 129 ng/ml; hence, a reporting level of 5 ng/ml was suggested to support the distinction between the permitted and prohibited use of the glucocorticoid 166 . Investigations into the elimination of the legitimate use of intraarticular THA applications however demonstrated that urinary TA was determined at levels exceeding 30 ng/ml for up to 4 days.…”
Section: Corticoids and Cannabinoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…All glucocorticoids are prohibited in‐competition if administered systemically and, consequently, the means to attribute an adverse analytical finding to both in‐competition use and systemic administration are required. Hence, elimination profiles for triamcinolone hexacetonide as well as prednisone and prednisolone were studied, aiming to identify diagnostic drug and/or metabolite patterns or concentrations. Another complicating factor was addressed in the case of prednisone and prednisolone, which occasionally originate from in situ microbial transformations of naturally occurring endogenous steroids.…”
mentioning
confidence: 99%